Soya-maize-sorghum ready-to-use therapeutic food (SMS-RUTF) for the management of severe acute malnutrition among children: A systematic review and meta-analysis - Tsurayya, Ghina; Nazhifah, Cut A.; Pirwanja, Muhammad R.; Lemu, Yohannes K. (Narra Sains Indonesia, 2023)
In managing severe acute malnutrition (SAM) among children, the World Health Organization has endorsed the use of ready-to-use therapeutic foods (RUTF), especially the peanut and milk-based (PM-RUTF), which has been proven for its efficacy. Unfortunately, the distribution of PM-RUTF is challenged by high financial cost and reliance on imports for milk and peanuts. Researchers explore the Soy-Maize-Sorghum (SMS)-RUTF as the alternative, in which the formulation has two types; milk-free soya-maize-sorghum (FSMS)-RUTF and low milk content SMS (MSMS)-RUTF. The aim of this study was to evaluate the efficacy, safety, and acceptance of SMS-RUTFs in the management of SAM among children as compared with PM-RUTF. Eligible studies were searched through PubMed, Scopus, and Embase up to July 14, 2023. Studies reporting the effects of SMS-RUTF, FSMS-RUTF, or MSMS-RUTF intake on SAM with PM-RUTF as the control were considered eligible. The included randomized controlled trials were then assessed for the risk of bias using Cochrane Risk of Bias 2.0. Odds Ratio (OR) and mean difference (MD) were calculated using a random-effects meta-analysis. The analysis focused on investigating the recovery, mortality, weight gain, and hemoglobin levels. Five randomized controlled trials involving a total of 5,513 children were incorporated in this review. Of which, four studies were included in the statistical analysis. Those receiving SMS-RUTF was 0.77 times less likely to recover from SAM as compared to control (95% CI: 0.66–0.90, p<0.01). The SMS-RUTF group had 1 kg lower weight gain as compared to control (95% CI: -1.25–0.75, p<0.01). However, the SMS-RUTF group had significantly higher increase of hemoglobin level than control (MD: 0.80 g/dL [95% CI: 0.68–0.93], p<0.01). Adverse effects were observed similar in both SMS-RUFT and control groups. SMS-RUFT received low acceptance from the participants suspected to be caused by poor packaging. In conclusion, SMS-RUTF is less effective than PM-RUTF in managing SAM among children but can be used to improve anemia as indicated by increased hemoglobin levels.